Pengaruh Kepemimpinan Transformasional, Disiplin Kerja dan Semangat Kerja Terhadap Kinerja Anggota pada Satuan Hubdam VII/Wirabuana - Moh. Anwar; Muhammad Nuzul Qadri; Ummy Kalsum (SIGMA: Journal of Economic and Business, 2018)
This study aims to identifity and explain the effect of transformational leadership, work discipline and morale of the performance of members of the Hubdam Unit VII/ Wirabuana. The population in this study are all members of the Hubdam Unit VII / Wirabuana totaling 163 people. This study uses linear regression analysis. The results showed that : (1) Transformational leadership, work discipline and morale affect the performance of members in Hubdam Unit VII / Wirabuana. (2) Leadership transformational effect on the performance of members of the Hubdam Unit VII / Wirabuana. (3) Discipline influential work on the performance of member in Hubdam Unit VII / Wirabuana. (4) Morale affect the performance of members in Hubdam Unit VII / Wirabuana.